OTOMATISASI PROSES PEMBUATAN SURAT JALAN DI AUTO WAREHOUSE SECTION PT. IKPP SERANG DENGAN MENGINTEGRASIKAN DATA ORDER PADA SAP R/3 DAN DATA HASIL PEMUATAN KONTAINER PADA APLIKSI CONTAINER PLANNING - Rehulina Tarigan (Teknik Informatika Fakultas Ilmu Komputer, 2018)
ABSTRAK Data integration is needed on different application systems and database platforms to maintain synchronization and data consistency in both systems. PT Indah Kiat Pulp & Paper (PT. IKPP) Serang has implemented SAP R / 3 as a software to support its business processes and operational activities more efficiently and effectively. But not all operational activities can be carried out on SAP, for example container simulation process to get the minimum number of containers in the delivery of goods. This happened in the Auto Warehouse section when the officer did picking and packing. The input data during the picking and packing process in SAP is the scan result of the label loading of goods into containers that is carried out in Container Planning applications as a non SAP system to be able to print travel documents. The problem that often occurs is the process of picking and packing through many steps and requiring a long time, human error occurs when inputting data so the data is out of sync. As a result, there was a delay in printing the travel documents so that the containers could not leave immediately and there were customer complaints due to incorrect specifications and the number of items. In this connection there are some interesting questions: How to synchronize order data on SAP with actual shipping data as a result of loading into containers in Container Planning. How to simplify the process of picking and packing for making travel documents. In this paper, the author tries to analyze the subject matter, analyzes the program interface with the Batch Data Communication method for integration. The results are intended to be implemented in the Auto Warehouse section so that it can shorten the time to make the travel documents and reduce customer complaints due to incorrect shipments.